Probabilidade implícita de default em debêntures do mercado brasileiro - Fernandez, Paulo Ramiro S. (2014)
This work aims to extract implicit default probabilities curves from Brazilian´s debentures market. This process occurs in two steps. First challenge is to obtain the term structure of Brazilian’s debentures. Diebold and Li (2006) proposed a revision of Nelson and Siegel (1987) parametrical model. To extract the term structure of Brazilian´s debentures, Diebold and Li (2006) work was used as guidance. The second step consists in extract the default probability using the reduced form model proposed by Duffie and Singleton (1999). Some assumptions were considered, such as loss fraction rate as a constant. The same assumption was considered by Xu and Nencioni (2000). Moreover, the exponential decay rate was fixed as suggested by Araújo (2012). The exercise was replied in three distinguished dates during the Brazilian interest rate reduction cycle. One of the results from this work was that the market agents considered a reduction on the default probability during the reduction cycle. The reduction in short term was greater than long term.